2017
DOI: 10.15403/jgld.2014.1121.264.hpy
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of White Light Endoscopy, Chromoendoscopy and Magnifying Endoscopy with Narrow Band Imaging in the Diagnosis of Early Gastric Cancer after Helicobacter pylori Eradication

Abstract: Background & Aim: Early-stage gastric cancer (EGC) found after H. pylori eradication often has non-tumorous epithelium on the tumorous tissue and/or surface differentiation of tumors, which may confuse endoscopic and histologic diagnosis. We investigated the diagnostic reliability of EGC using conventional white light endoscopy (WLE), chromoendoscopy (CE) using indigo carmine, and magnifying endoscopy with narrow band imaging (ME-NBI) in patients with EGC with or without history of prior H. pylori eradicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
6
20
0
Order By: Relevance
“…Our result indicate that combining ME-NBI with WLE can predict pathological findings of gastric lesions in such clinical conditions with higher sensitivity, specificity and high confidence, which can reduce the number of endoscopic biopsy and can shorten the examination time. We showed that frequency of diagnosed case, as well as diagnostic yield of EGC, were not improved when combining CE with WLE compared to WLE alone, which was in line with our previous retrospective study [14]. Since the diagnosis of EGC using the conventional WLE and the CE is based on endoscopic findings of irregularly shaped depression or unevenness elevation, which are often accompanied with a color change (reddish or whitish).…”
Section: Prospective Studysupporting
confidence: 88%
See 4 more Smart Citations
“…Our result indicate that combining ME-NBI with WLE can predict pathological findings of gastric lesions in such clinical conditions with higher sensitivity, specificity and high confidence, which can reduce the number of endoscopic biopsy and can shorten the examination time. We showed that frequency of diagnosed case, as well as diagnostic yield of EGC, were not improved when combining CE with WLE compared to WLE alone, which was in line with our previous retrospective study [14]. Since the diagnosis of EGC using the conventional WLE and the CE is based on endoscopic findings of irregularly shaped depression or unevenness elevation, which are often accompanied with a color change (reddish or whitish).…”
Section: Prospective Studysupporting
confidence: 88%
“…The cohort consisted of 71 EGCs from 61 patients after H. pylori eradication (eradication group) and 115 EGCs with current H. pylori infection (control group). Diagnostic yield of EGC by using ME-NBI was 88.7% (63/71) in the eradication group, which was significantly lower than that of control group (98.2%: 113/115, P=0.01) [14]. This result seemed to be similar to those reported in others study, reporting that approximately 10 % of EGCs after H. pylori eradication were difficult to diagnose using ME-NBI [15].…”
Section: Retrospective Studysupporting
confidence: 86%
See 3 more Smart Citations